2014
DOI: 10.5812/jjm.14004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genotyping of Shigella sonnei Strains Isolated From Children With Bloody Diarrhea Using Pulsed Field Gel Electrophoresis on the Total Genome and PCR-RFLP of IpaH and IpaBCD Genes

Abstract: Background:Identification, understanding of antibiotic sensitivity patterns and molecular characterization of genetic elements of Shigella species are important because of both epidemiological and clinical indications in developing countries.Objectives:The aim of this study was to analyze molecular epidemiology of Shigella isolates recovered from children with diarrhea in Shiraz (Southern Iran), using IpaH and IpaBCD PCR-restriction fragment length polymorphism (RFLP), and to determine pulsed field gel electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 30 publications
4
13
0
4
Order By: Relevance
“…The ipaH gene is present in numerous copies in the chromosome and in the virulence plasmid of species of the genus Shigella, and is associated with the invasion of bacteria into host cells (Cruz et al, 2014;Farshad et al, 2015). The ipaBCD and ial plasmidial genes are responsible for the invasion of species of the genus Shigella (Campos et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The ipaH gene is present in numerous copies in the chromosome and in the virulence plasmid of species of the genus Shigella, and is associated with the invasion of bacteria into host cells (Cruz et al, 2014;Farshad et al, 2015). The ipaBCD and ial plasmidial genes are responsible for the invasion of species of the genus Shigella (Campos et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Ampicillin and sulfamethoxazole-trimethoprim are commonly used as the first-line drugs for the therapy of shigellosis while second-line drugs including the third generation of cephlosporines and fluoroquinolones are used for the treatment of children and adults respectively (11,16). Unluckily, it has been recently reported that the prevalence of resistance to some commonly used antibiotics is increasing in Shigella spp in Iran (17,18 (5,11,19). In our study, the prevalence of ESBL producing Shigella isolates accounted for 11.4 % of all Shigella isolates which is larger than the reports from Iran and other countries (11,20,21).…”
Section: Discussionmentioning
confidence: 99%
“…S. flexneri is the most common agent of shigellosis in developing countries and tropical areas (e.g., Iran). However, epidemiological shift in shigellosis and the change in the pattern of antibiotic resistance among Shigella strains have been reported in recent years in Iran and the world (5,6). As with other infectious diarrheal diseases, treatment of shigellosis includes both rehydration and antibiotics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the presence of these repetitive extragenic palindromic sequences, by designing an appropriate primer according to desired sequence using PCR, electrophoresis of the resultant PCR products, and gel analysis by computer (6)(7)(8)(9) and given the number of sequences in each strain and their difference in length, the number of bonds obtained by PCR for each strain is different, and therefore the strains are classified based on diversity of bonds. Although, use of PFGE is considered as a gold standard method, the REP-PCR is a simpler and lower-cost method and provides more rapid results (11).…”
Section: Introductionmentioning
confidence: 99%